Respuesta :

Answer:

x = -3

Step-by-step explanation:

3x - 21 = 2x - 24

3x = 2x - 3

x = -3

Answer:

x = 45

Step-by-step explanation:

First, we need to use the distributive property on both sides of the equation. We multiply the number outside of the parentheses by every term inside the parentheses.

3(x - 7) = 2(x - 12)

3x - 21 = 2x - 24    

From here, we solve for x.

3x - 21 = 2x - 24

x - 21 = 24                 (Subtract 2x from both sides)        

x = 45                       (Add 21 to both sides)

ACCESS MORE